PEMETAAN DAN PENGARUH KEBISINGAN TERHADAP KELELAHAN KERJA KARYAWAN PADA BAGIAN FIBERLINE DI INDUSTRI PEMBUATAN BUBUR KERTAS - Trisna, Trisna; Erliana, Cut Ita; Lestari, Renny (Jurnal Sistem Teknik Industri, 2017)
Manpower is an element that is dealing directly with the various consequences of industrial activities undertaken. Unqualified physical work environment such as noise that has exceeded the NAV is one of the examples faced by the workforce in the workplace. One of the activities that produce noise is the activity in the fiberline department in the pulp making industry which is the pulp making area. This study aims to map the noise and its effect on employee fatigue in the pulp making industry in the fiberline department. Research stages include noise measurement, noise mapping, filling out questionnaires by employees about work fatigue, calculation of questionnaire results, determining the effect of noise and work fatigue with regression analysis, and correlation determination. The noise mapping results at 30 point measurements indicate that the bleaching and pulp engine border areas exceed the safe threshold noise. Regression analysis results show the higher the noise level, the higher the level of work fatigue in employees. The result of correlation analysis is known that the correlation is positive or strongly correlated which shows that the effect of noise on fatigue is very strong. The noise mapping results can be known which area exceeds the noise threshold, so the company can anticipate the negative impact, as well as the strong relationship between noise and work fatigue.